Systematic Review of Cardiovascular Outcomes with Sulfonylureas, GLP-1 RA, and DPP-4 Inhibitors in Type 2 Diabetes Mellitus - Koo Thai Hau; Mohamed Mafauzy; Leong Xue Bin (Journal of Diabetology)
Type 2 diabetes mellitus (T2DM) significantly increases the risk of cardiovascular diseases. Despite advances in glycemic control, managing cardiovascular risk remains a critical challenge. This systematic review aims to assess and compare the cardiovascular outcomes associated with three classes of antidiabetic medications: sulfonylureas, Glucagon-like peptide-1 receptor agonists (GLP-1 RAs), and dipeptidyl peptidase-4 inhibitors (DPP-4i) in patients with T2DM. A systematic review was conducted following the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. Electronic databases, including PubMed, Embase, Cochrane Library, and Google Scholar, were searched for relevant studies published between 2019 and 2023. Inclusion criteria were adults (≥18 years) with T2DM, studies assessing cardiovascular outcomes with the specified medications, randomized controlled trials, observational studies, or meta-analyses. Two independent reviewers performed data extraction and risk of bias assessments. From the initial 1,543 records, 12 studies were included involving 61,534 patients. As a result, GLP-1 RAs demonstrated favorable cardiovascular safety and efficacy, particularly in reducing major adverse cardiovascular events and all-cause mortality. DPP-4 inhibitors were associated with neutral cardiovascular outcomes but indicated an elevated risk of cardiac failure in some studies. In recent studies, sulfonylureas, previously associated with cardiovascular concerns, showed no consistent evidence of increased cardiovascular risk. These findings highlight the importance of personalized treatment strategies to optimize cardiovascular outcomes in patients with T2DM.